Emerging technologies in face and body contouring - Theodorou, Spero J.; Chia, Christopher T.; Dayan, Erez (Thieme, 2021)
"Emerging Technologies in Face and Body Contouring by internationally acclaimed experts Spero Theodorou, Christopher Chia, Erez Dayan and esteemed contributors, details emerging state-of-the-art technologies in minimally-invasive body contouring. This resource fills a void in the literature, providing plastic, aesthetic, and dermatologic surgeons with clinical insights on the latest proven techniques in nonsurgical fat reduction and skin tightening. The book begins with chapters on 3D imaging for emerging body contouring technologies, clinically applicable concepts of fat metabolism, and discussion of laser and ultrasound. Procedural chapters cover a diverse array of cutting-edge noninvasive body contouring and VASER techniques, including water-assisted and power-assisted liposuction. Chapters dedicated to the face and neck detail scarless face lifting, injection lipolysis, and radiofrequency skin tightening. Body-specific chapters focus on the neck, arms, abdomen, flanks and hips, gluteal region, thighs and calves, ankles and knees"--